Features of the flora and vegetation of the Pyatigorye’s upland steppes (ecoregion of the Caucasian Mineral Waters) - V. N. Belous (Проблемы ботаники Южной Сибири и Монголии, 2021)
The article deals with the issues of localization and landscape preference of Pyatigorye’s phytocenoses ofthe upland steppes. The syntaxonomic composition of the steppe communities on the studied territory, as well as the typesof the floristic core, are indicated. It consists of graminoids, mesothermal perennials of long vegetation, caudex herbs ofan ephemeroid type of development, and bulbous geophytes. The features of communities, the reasons for their spatialdifferentiation are revealed. The distribution of species by relief elements and communities was determined expertlyon the basis of field studies (2018–2021). It was concluded that the main factors determining the diversity of uplandsteppe vegetation in the studied region are the nature of the destruction of the parent rock and soil development, the levelof insolation and ecotope moisture. The steppe communities of Pyatigorye on carbonate underdeveloped thin skeletalchernozems are distinguished by their species richness. In most of them, Stipa pulcherrima plays a high phytocenotic role,as well as other sod and dense bush grasses. Species of the “southern” steppe and Caucasian forbs, incl. petrophytes playsignificant role. The communities include rare species in the region: Astragalus brachycarpus, Dictamnus gymnostylis,Leopoldia tenuiflora, Paeonia tenuifolia, Iris pumila, I. aphylla, Orchis tridentata, Asphodeline taurica, Lamyra echinocephala,Linum tauricum, Onosma caucasica, Cerasus incana, Cephalaria coriacea. The studied representative communities areimportant for the conservation of the biological diversity of the region. Habitats of rare species are of scientific importanceand are of nature conservation interest.